Characterization of Bioplastics from Breadfruit (Artocarpus altilis) Starch and Carboxy Methyl Cellulose (CMC) with Glycerol Plasticizer - Cut Fatimah Zuhra; Suhadiman Dwi Baruna (Talenta Publisher, 2023)
Research on the synthesis of bioplastic from breadfruit (Artocarpus altilis) starch and carboxy methyl cellulose (CMC) has been successfully carried out with the addition of glycerol. Samples are conducted by varying the glycerol concentrations (10%, 20%, 30%, and 40%) at 60oC, respectively. The bioplastic product was tested using tensile strength, elongation, water content absorption, biodegradability, and Fourier transform-infra infrared (FT-IR). The tensile strength properties from bioplastic result evaluated is 34.26 N/mm2. The elongation at break of bioplastic is found at 21.4%. Water content results from bioplastic of 44%. Biodegradability study that bioplastics of 20% in 32 days. Correspondingly, the FT-IR confirmed the functional groups of bioplastics from breadfruit starch and CMC with glycerol.